Regional features of electrocardiostimulation: some results and resource search (Mordovia population example) - A. A. Alexandrovsky; M. D. Romanov; M. Yu. Morozov; E. V. Kolpakov; T. A. Kuznechik; A. V. Ryndina (Российский кардиологический журнал)
So far, electrocardiostimulation (ECS) problems, and their regional solutions, have been inadequately described. Therefore, the aim of this study was to investigate short- and long-term ECS results in patients of Saransk City and Mordovia Republic regions; to search for methods improving end-points in these patients. The study included 51 ECS individuals who underwent pacemaker implantation at Saransk City Clinical Hospital No. 4 (1996-2004). Questionnaire survey and clinical follow-up methods were used; ECS concept was reviewed: intervention indications, short- and long-term complications, their diagnostics, treatment and prevention; recommendations for controlling the problems identified were developed. Unfortunately, Russian standards of diagnostics, treatment (including surgery), and out-patient follow-up of such patients have not been created yet. Organizing a Saransk branch of Research Institute of Transplantology and Artificial Organs, including a modern telemedicine complex, might be an optimal regional-level solution for these problems.